Atheroprotective and atheroregressive potential of azapeptide derivatives of GHRP-6 as selective CD36 ligands in apolipoprotein E-deficient mice. (August 2020) - Frégeau, Geneviève; Sarduy, Roger; Elimam, Hanan; Esposito, Cloé L.; Mellal, Katia; Ménard, Liliane; Leitão da Graça, Silas D.; Proulx, Caroline; Zhang, Jinqiang; Febbraio, Maria; Soto, Yosdel; Lubell, William D.; et al.
Abstract: Background and aims: Scavenger receptor class B member 3, also known as cluster of differentiation-36 (CD36) receptor, is involved in the uptake and accumulation of modified lipoprotein in macrophages, driving atherosclerosis progression. Azapeptide analogs of growth hormone-releasing peptide-6 (GHRP-6) have been developed as selective CD36 ligands and evaluated for their anti-atherosclerotic properties in apoe −/− mice. Methods: From 4 to 19 weeks of age, male apoe −/− mice were fed a high fat high cholesterol (HFHC) diet, then switched to normal chow and treated daily with 300 nmol/kg of MPE-001 ([aza-Tyr 4 ]-GHRP-6) or MPE-003 ([aza-( N, N -diallylaminobut-2-ynyl)Gly 4 ]-GHRP-6) for 9 weeks. In another protocol, mice were fed a HFHC diet throughout the study. Results: Azapeptides decreased lesion progression in the aortic arch and reduced aortic sinus lesion areas below pre-existing lesions levels in apoe −/− mice which were switched to chow diet . In mice fed a HFHC throughout the study, azapeptides reduced lesion progression in the aortic vessel and sinus. The anti-atherosclerotic effect of azapeptides was associated with a reduced ratio of iNOS + /CD206 + macrophages within lesions, and lowered plasma inflammatory cytokine levels. Monocytes from azapeptide-treated mice showed altered mitochondrial oxygen consumption rates, consistent with an M2-like phenotype. These effects were dependent on CD36, and not observed in apoe −/− cd36 −/− mice. Conclusions: Azapeptides MPE-001 and MPE-003 diminished aortic lesion progression and reduced, below pre-existing levels, lesions in the aortic sinus of atherosclerotic mice. A relative increase of M2-like macrophages was observed in lesions, associated with reduced systemic inflammation. Development of CD36-selective azapeptide ligands merits consideration for treating atherosclerotic disease. Graphical abstract: Image 1 Highlights: Azapeptide analogs of GHRP-6 were synthesized as selective CD36 ligands. Azapeptides elicit lesion regression in aortic sinus in a CD36-dependent manner. Azapeptides halted atherosclerotic lesion development in aorta. Azapeptides induce macrophage skewing towards the anti-inflammatory phenotype.